Thoracoscopy: Advances and Increasing Role for Interventional Pulmonologists - Lee, Pyng; Folch, Erik (Seminars in Respiratory and Critical Care Medicine, 2018)
Thoracoscopy is an increasingly common procedure that provides significant clinical information and therapeutic applications. The procedure allows the physician to biopsy the parietal pleura under direct visualization with high accuracy. In addition, one can drain pleural fluid, place a chest tube in a precise location, and perform poudrage pleurodesis. Medical thoracoscopy (MT) is carried out in the operating room or procedure suite under moderate sedation with spontaneous ventilation. In comparison, video-assisted thoracoscopic surgery (VATS) is performed under general anesthesia with single lung ventilation and through multiple ports in the operating room. MT is less invasive, has a comparable diagnostic yield, and may be better tolerated in high-risk patients. The indications, complications, and advances in thoracoscopy will be discussed in this article. In the era of rapidly evolving therapeutics for lung cancer, immune-modulation and ever-increasing risks of immunosuppression, MT will evolve and continue to play a pivotal role in the evaluation and research of pleuropulmonary diseases.
Keywords: thoracoscopy; pleural effusion; video-assisted thoracoscopic surgery (VATS); pleuroscopy; malignant pleural effusion; empyema